Kompetensi Manajerial Kepala Madrasah Dalam Meningkatkan Jabatan Fungsional Guru - Rochmani; Engkus Kuswarno; Nanang Hanafiah; U. Supyan Sauri (TANZHIMUNA : Jurnal Manajemen Pendidikan Islam, 2021)
This research is motivated by the phenomenon of the lack of knowledge or the ability of teachers in making scientific papers, which causes obstruction of the promotion of functional positions of teachers from class IV / a to group IV / b. The approach used in this research is a qualitative approach with descriptive analysis method. The data collection technique is done through observation, interview and documentation study. The results showed that: 1) Forecasting used is a type of "Demand Forecasting", Forecasting is based on long, medium and short term time horizons. However, it does not meet the criteria of good forecasting, that is, it does not meet the standard of accuracy, cost and convenience forecasting. 2) Planning has been implemented properly through the 5W1H answer technique, but the results are not optimal. 3) Organizing has been carried out by compiling the Madrasah organizational structure, but there is no specific organizational structure to facilitate the implementation and coordination of the teacher functional position promotion program. 4) Controlling or control in Madrasah has been carried out through supervision activities, but it is not optimal, because the supervision is not in accordance with standard operating procedures and only to meet administrative reporting needs. 5) Commanding or briefing is carried out by involving civil servant teachers in education and training activities, as well as fostering and motivating PNS teachers to increase the number of credit scores, but the results of the coaching are not optimal. 6) Coordinating or coordination in Madrasahs has been carried out vertically, both internal and external, but the implementation has not been optimal.